2020
DOI: 10.20473/jde.v5i2.18275
|View full text |Cite
|
Sign up to set email alerts
|

Causality Between Gross Domestic Product, Exports, Imports, Foreign Exchange Reserves, and Foreign Debt in Indonesia

Abstract: This research aims to determine the relationship between gross domestic product, exports, imports, foreign exchange reserves, and foreign debt in Indonesia from 1978 – 2018. As a developed country, Indonesia must know the interrelatedness between the GDP and the variable in the international balance of payment to move the economy well. This research using the Vector Autoregression (VAR) method that includes ADF Test, Granger Causality, Johanssen Co-integration, Vector Error Correction Model (VECM), and forecas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Experts interpret national income as the part of people's income that is used for consumption and saving; therefore, income affects the amount of savings in banking institutions (Arrohmah & Soelistyo, 2010). National income is identified based on gross domestic product (GDP), which is the result of the sum of consumption, investment, and government expenditure as well as the deviation between exports and imports (Syukri, 2020;Taqiuddin, 2019). This study examined market concentration, company size, and financing risk to determine the profitability of Indonesian and Malaysian Islamic banks by using GDP as a control variable.…”
Section: National Incomementioning
confidence: 99%
“…Experts interpret national income as the part of people's income that is used for consumption and saving; therefore, income affects the amount of savings in banking institutions (Arrohmah & Soelistyo, 2010). National income is identified based on gross domestic product (GDP), which is the result of the sum of consumption, investment, and government expenditure as well as the deviation between exports and imports (Syukri, 2020;Taqiuddin, 2019). This study examined market concentration, company size, and financing risk to determine the profitability of Indonesian and Malaysian Islamic banks by using GDP as a control variable.…”
Section: National Incomementioning
confidence: 99%
“…There is a relationship between GDP and foreign debt where the relationship is shown that when there is a shock to GDP it will have an impact on foreign debt. So this needs to be considered by the government in managing debt for things that benefit the country that not only increases state funding (Syukri, 2020). The use of debt funds to productive matters such as infrastructure development will increase GDP growth.…”
Section: Literature Reviewmentioning
confidence: 99%